Country‐of‐origin, localization, or dominance effect? An empirical investigation of HRM practices in foreign subsidiaries - Pudelko, Markus; Harzing, Anne‐Wil (Human Resource Management, 2007)
AbstractThis article contributes to two recurring and very central debates in the international management literature: the convergence vs. divergence debate and the standardization vs. localization debate. Using a large‐scale sample of multinationals headquartered in the United States, Japan, and Germany, as well as subsidiaries of multinationals from these three countries in the two other respective countries, we test the extent to which HRM practices in subsidiaries are characterized by country‐of‐origin, localization, and dominance effects. Our results show that overall the dominance effect is most important (i.e., subsidiary practices appear to converge to the dominant U.S. practices). Hence, our results lead to the rather surprising conclusion for what might be considered to be the most localized of functions—HRM—that convergence to a worldwide best practices model is clearly present. The lack of country‐of‐origin effects for Japanese and German multinationals leads us to a conclusion that is of significant theoretical as well as practical relevance. Multinationals might limit the export of country‐of‐origin practices to their core competences and converge to best practices in other areas. © 2007 Wiley Periodicals, Inc.